ARTICLE REVIEW PERDARAHAN SUBKONJUNGTIVA - Syiva Ulhayah; Rani Himayani; Putu Ristyaning Ayu Sangging (CV. Jasa Sukses Abadi, 2023)
One of the common complaints in emergency departments and outpatient clinics is red eyes. One of the causes of red eyes that often occurs is subconjunctival hemorrhage which is a disorder that can occur in most benign situations but can also occur at certain times as a clinical manifestation of a diagnosis of a dangerous disease, especially if the bleeding occurs continuously or recurrently. . Usually, subconjunctival hemorrhages are painless. The conjunctiva consists of two parts, namely the bulbar part which covers the sclera and the tarsal part which covers the inside of the eyelids. The occurrence of subconjunctival hemorrhage is due to tearing of the small blood vessels on the surface of the eye above the sclera. This leaking blood then enters the lower Tenon's capsule and its condition becomes more pronounced when the blood leaks into the externally exposed portion of the bulbar conjunctiva. Subconjunctival hemorrhage can occur in elderly or young patients where the main risk factors in young patients are trauma and contact lens use and in elderly patients are systemic vascular diseases, such as hypertension, diabetes, and arteriosclerosis. In its treatment, subconjunctival hemorrhage does not require special treatment and will heal within 1-2 weeks. However, several factors need to be considered in the management of subconjunctival hemorrhage, including whether the patient experiences irritation, whether subconjunctival bleeding is accompanied by decreased vision, and whether there is a history of trauma. Subconjunctival hemorrhage has a good prognosis.